Desorption of zinc, copper and lead ions from loaded flax fibres. Issue 12 (25th May 2023) - Kajeiou, Meriem; Alem, Abdellah; Mezghich, Soumaya; Ahfir, Nasre-Dine; Mignot, Mélanie; Pantet, Anne
ABSTRACT: Biosorption is an efficient and cost-effective method for heavy metals' remediation. However, saturated biosorbents may pose a serious problem for the environment. Flax fibres have shown very good adsorption capacities to remove zinc, copper and lead ions from contaminated aqueous solutions. In this study, adsorption–desorption cycles were conducted with loaded flax fibres in batch mode to recover heavy metals using four types of solutions: hydrochloric acid solution, nitric acid solution, sodium hydroxide solution and ultrapure water. Desorption kinetic studies, conducted with loaded flax fibres, showed very fast desorption of zinc, copper and lead when using nitric and hydrochloric acids with a selectivity sequence of Zn (totally desorbed) > Cu (94%) > Pb (80–73%). Desorption kinetic was slower with the use of sodium hydroxide and showed much lower desorption rates of Zn (62%) > Pb (12%) > Cu (7%). Desorption of zinc and copper from previously loaded fibres from binary metal ion system in lead solution was also investigated. Different concentrations ranging from 0.04 to 0.20 mmol/L were tested. The obtained results demonstrated a significant release in the order Zn (18–90%) > Cu (2–42%), while lead was still efficiently adsorbed. Retention efficiencies of zinc and copper and adsorption efficiency of lead resulted in the same adsorption efficiencies of the three metal ions onto flax fibres in the ternary metal ion system.